Heavy Metal Content of Cadmium in Tilapia from Taliwang Swamp Lake, West Sumbawa Regency - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati (Jurnal Pijar Mipa, 2025)
Research on the heavy metal Cd in fish is crucial to protect humans as consumers from harmful health impacts. This study aimed to determine the cadmium (Cd) content in tilapia (Oreochromis mossambicus) from Taliwang Swamp Lake (TSL). The specific benefit of this study is to protect consumers who consume fish from Cd contamination. This study was conducted in TSL waters. There are two research stations, one located in the eastern part and the other in the western part of the lake. Data collection was carried out using gill nets. Four tilapia samples were taken at each station. The tilapia samples were then wrapped in plastic bags and stored in sample boxes. The research samples were then analyzed at the West Nusa Tenggara Health, Testing and Calibration Laboratory Center. Data analysis was carried out by taking tilapia muscle tissue and analyzing metal content, especially Cadmium (Cd), using an Atomic Absorption Spectrophotometer. Measurement of heavy metals in tilapia tissue was carried out by adding concentrated HNO3 and HClO4, heated at 60-70ºC for 2-3 hours until the solution became clear. The samples were ready to be measured by AAS using an air-acetylene flame. The conclusion of this study was that the heavy metal content of Cd in tilapia (O. mossambicus) originating from TSL was 0.03 mg/kg (ppm).